Clinical findings and outcomes of juvenile‐onset chronic kidney disease of unknown aetiology in dogs: a retrospective study of 36 cases (2010‐2023) - H. Miyakawa; M. Nakano; M. Ishizaka; A. Miyagawa; Y. Miyagawa; N. Takemura (Journal of Small Animal Practice, 2026)
Objectives To describe the clinical findings and outcomes of juvenile‐onset chronic kidney disease of unknown aetiology in dogs. Materials and Methods This retrospective study included 36 client‐owned dogs under 3 years of age with chronic kidney disease. In the observational cohort study, the signalment and clinicopathology findings in the dogs ( n = 36) were described. A longitudinal analysis ( n = 28) was performed to investigate the time to chronic kidney disease progression and death. The risk of chronic kidney disease progression defined as increased >25% of serum creatinine concentration was calculated using the Cox proportional hazard model. Results The most common breeds were Labrador retrievers and Shetland sheepdogs ( n = 5, respectively). Seven dogs were classified as chronic kidney disease stage 1, 17 as stage 2, eight as stage 3 and four as stage 4 according to International Renal Interest Society guidelines. The prevalence of proteinuria (urine protein:creatinine ratio ≥ 0.5) was 35%. None of the dogs had an indirect systolic blood pressure ≥ 160 mmHg. Serum total calcium concentration at presentation was positively associated with the risk for chronic kidney disease progression (hazard ratio, 2.24; 95% confidence interval, 1.11 to 4.53; P = .03). All dogs with chronic kidney disease stage 3 experienced progression to stage 4. Overall, the median survival time (95% confidence interval) was 1461 days (530 to 2620 days). Clinical Significance Juvenile‐onset chronic kidney disease of unknown aetiology was diagnosed in the various breeds of dogs. The prevalence of hypertension was lower than reported in previous studies. Serum total calcium concentration at presentation was associated with the risk of chronic kidney disease progression. Our study provides useful information on the characteristics and outcomes of canine juvenile‐onset chronic kidney disease.